APPLICATION OF THE HERMENEUTIC METHOD IN CONTEMPORARY EDUCOLOGY SCIENCE - Juodaitytė, Audronė; Savickis, Antanas (Acta Paedagogica Vilnensia, 2013)
One of the most important research methods for the science of education studies today is hermeneutics, expressing the understanding of interpretations and encompassing the discourse analysis. It is inseparable from texts. Interviews and even analyses of human actions are treated as texts. Applying the hermeneutic method, the focus is on a priori understanding of the text. The researcher’s influence on the perception of its meanings becomes inevitable. This enables to increasingly approach the concrete truth, the concrete pragmatic meanings of the study subject. Qualitative hermeneutic researches in the science of education studies help to postulate the necessity of the pluralistic evaluation of facts, to release the researcher from limitations made by empiricist models. As a result, this leads to understanding the possibilities of the research and the consequent perception and enables the research to exist freely, independently of the conceptions of dogmatic meanings. Then, thanks to hermeneutics, the science of education studies becomes able to turn collected knowledge into understanding accessible not only to scientists, but also to as broad as possible community representing human discourses.